Investigation of a novel natural convection heat sink for LEDs based on U-shaped mini-heat pipe arrays. (5th March 2022) - Jiu, Yuan; Fan, Hongming; Wang, Wei
Highlights: A novel heat sink based on mini-heat pipe array is proposed and tested. Substrate temperature of LED can be reduced below 70 °C when the input power is 100 W. The effect of heat sink structure on thermal performance is discussed. Abstract: The increasing use of light-emitting diodes (LEDs) requires advances in heat dissipation. Previous applications of heat pipes for LED cooling faced the challenges of contact thermal resistance and insufficient heat transfer areas. In this study, a novel heat sink based on a mini-heat pipe array (MHPA) is proposed, which can overcome these challenges. The thermal performance of the heat sink was experimentally tested. The substrate temperature can be reduced below 70 °C when the input power is 100 W. MHPA shows good temperature uniformity. When the input power is 100 W and 200 W, the maximum temperature drops of MHPA in the vertical direction are 0.6 °C and 1.1 °C, respectively. A numerical model was established and validated. The effect of the heat sink structure was investigated using numerical methods. A higher fin height and more cross-cuts can enhance heat transfer. When the fin pitch is less than 10 mm, increasing the pitch is beneficial to heat transfer. Appropriate use of variable fins can enhance heat transfer. Orthogonal tests are designed to find the optimal heat sink structure. The optimal structure has a fin pitch of 8 mm, a fin height of 43 mm, a fin thickness of 0.5 mm, 40% of the variable fins, and 6 cross-cuts.